Pemetaan Status Kesuburan Tanah Sawah Berbasis Sistem Informasi Geografis di Subak Buaji dan Subak Padanggalak Kecamatan Denpasar Timur - SIREGAR, ELDO GABRIEL; ADI, I GUSTI PUTU RATNA; SUPADMA, A.A. NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.1, Januari 2021, 2021)
The Mapping of Paddy Soil Fertility Status Based on Geographic Information System in Subak Buaji and Subak Padanggalak, East Denpasar District This study aims to evaluate the status of soil fertility and provide management measures for limiting factors as well as making maps of soil fertility status in Subak Buaji and Subak Padanggalak, East Denpasar District. The method used in soil sampling in the study area is the survey method by first creating a homogeneous land unit obtained by overlaying several thematic maps such as semi-detailed soil maps, slope maps and subak maps, then each homogeneous land unit is carried out several observation points and Soil sampling using purposive sampling method which is then composited. Soil samples that have been obtained are then analyzed in the laboratory for soil chemical properties including: Cation Exchange Capacity (CEC), Base Saturation (KB), C-Organic Soil, P-total, K-total. The results of the analysis of soil chemical parameters are then evaluated on their fertility status based on the PPT technical guidelines for mapping soil fertility status (1995). The results showed that in Subak Buaji and Subak Padanggalak, East Denpasar District, there were three classes of soil fertility status, namely low fertility class (R) found in SLH I.II (Subak Padanggalak), medium fertility class (S) in SLH I.I (Subak Buaji ), while the high fertility class (T) is found in SLH II (Subak Buaji and Subak Padanggalak) and SLH III (Subak Padanggalak). The soil fertility parameter which is the limiting factor is the low P-total value. Management action to overcome these limiting factors is the addition of phosphorus fertilizers and organic fertilizers.